Soil Moisture Monitoring and Controlling System for Cultivation - จำปาทอง, ศราวุฒิ; ทองใหญ่, ปรารถนาดี; บุญประเสริฐ, จิรกรณ์; ใจดี, อนุวัฒน์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research addresses the critical challenges of water management in Thai agriculture, a key factor influencing crop growth and quality. Traditional manual irrigation relies heavily on individual experience and is increasingly threatened by climate change-induced water scarcity. To mitigate these issues, an IoT-based "Soil Moisture Monitoring and Controlling System for Cultivation" was developed, specifically optimized for salad vegetable greenhouses. The system utilizes the NodeMCU ESP8266 microcontroller as its core, integrated with a Capacitive Soil Moisture Sensor for enhanced precision and durability, and an Ultrasonic Sensor for tank water level monitoring. Data is transmitted via Wi-Fi to the Blynk Cloud platform for real-time monitoring and remote control. Experimental results demonstrate that the system maintains soil moisture within the optimal range (41% - 80%) effectively. Furthermore, a safety mechanism is implemented to deactivate the pump when water levels fall below 30%, preventing hardware damage. This automated system significantly reduces labor costs and operational burdens, representing a vital step toward data-driven, sustainable Smart Farming in Thailand.